Vlaamse reuzen. - Lefèvre, Pascal; de Maeyer, Gregie; Deviaene, Erna; Schoeters, Geertrui; Sollie, André ([S.l.] : Vlaamse Uitgevers Vereniging, 1998)
Aertssen, Kristien ; Baeten, Lieven ; Blancke, Jef ; Cneut, Carll ; Cotteleer, Erika ; De Bode, Ann ; de Maeyer, Gregie ; Meersman, Karel ; Decort, Vanessa ; Dendooven, Gerda ; Godon, Ingrid ; Lemmens, Riske ; Mathilde, Hilde [e.a.]
Cat. uitgeg. n.a.v. de Fiera del Libro per Ragazzi in Bologna 1998
kunstcatalogus
Keywords: Vlaanderen